2017
DOI: 10.17219/acem/63998
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of mutations in reverse transcriptase of hepatitis B virus is associated with liver disease severity in treatment-naïve Chinese patients with chronic hepatitis B

Abstract: Background. Mutations in reverse transcriptase (RT) of the hepatitis B virus (HBV) are demonstrated to be strongly associated with nucleos(t)ide analog resistance, which is supposed to be the biggest obstacle during the long-term anti-viral treatment of chronic hepatitis B. However, the presence of RT mutations in treatment-naïve chronic hepatitis B patients and its clinical significance are not well known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Zhao et al[ 27 ] also reported similar results showing that 75% of patients with RT mutations were HBeAg-negative and had lower HBV DNA levels (3.92 log 10 IU/mL) whereas 25% of patients with RT mutations were HBeAg-positive with higher HBV DNA loads (5.54 log 10 IU/mL). Similarly, Zhu et al[ 89 ] found that Chinese patients with chronic HBV carrying preexisting RT mutations had significantly decreased serum baseline HBV DNA loads ( P = 0.0363) and blood platelet counts ( P = 0.0181) compared with those without RT mutations.…”
Section: Clinical Factors (Hbeag Serostatus and Hbv Viral Loads) Affementioning
confidence: 90%
See 1 more Smart Citation
“…Zhao et al[ 27 ] also reported similar results showing that 75% of patients with RT mutations were HBeAg-negative and had lower HBV DNA levels (3.92 log 10 IU/mL) whereas 25% of patients with RT mutations were HBeAg-positive with higher HBV DNA loads (5.54 log 10 IU/mL). Similarly, Zhu et al[ 89 ] found that Chinese patients with chronic HBV carrying preexisting RT mutations had significantly decreased serum baseline HBV DNA loads ( P = 0.0363) and blood platelet counts ( P = 0.0181) compared with those without RT mutations.…”
Section: Clinical Factors (Hbeag Serostatus and Hbv Viral Loads) Affementioning
confidence: 90%
“…In addition, the number of RT mutations is associated with the liver disease progression. Zhu et al[ 89 ] revealed that patients with multiple RT mutant sites showed a significantly higher rate of liver fibrosis ( P = 0.0128), suggesting a link between viral mutation and clinical progression of chronic hepatitis, and also highlighting that the natural accumulation of RT mutations is a process involved in viral survival during chronic liver fibrosis.…”
Section: Preexisting Rt Mutations Are Related To the Progression Of Lmentioning
confidence: 99%
“…This data was consistent with several other previous studies, indicating that naturally occurring RT variants were associated with decreased HBV-DNA loads. 17,26,29 The reason may be that HBV replication is often impaired by the RT variants, which decreases the activity of polymerase. Although another study indicated that patients with multiple RT variants showed decreased HBV-DNA loads compared with patients with a single RT variant, 29 there was no difference in HBV-DNA loads and other clinical factors (gender, age, genotype, HBeAg, ALT, and AST levels) between the single variant and the multiple variants subgroups, implying that certain single RT variants played a crucial role in viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…17,26,29 The reason may be that HBV replication is often impaired by the RT variants, which decreases the activity of polymerase. Although another study indicated that patients with multiple RT variants showed decreased HBV-DNA loads compared with patients with a single RT variant, 29 there was no difference in HBV-DNA loads and other clinical factors (gender, age, genotype, HBeAg, ALT, and AST levels) between the single variant and the multiple variants subgroups, implying that certain single RT variants played a crucial role in viral replication. It is also worth noting that no classical primary and secondary variants were found in several previous studies, 14,29 which might have influenced the results of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…HBV pre-existing gene resistance has been confirmed by many studies [15][16][17], and the pre-existing mutation patterns of gene resistance are diverse [15]. However, there is no consensus on HBV genetic resistance testing before NAs antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%